Про перспективи використання замкнутих оборотних систем водопостачання цукрових заводів - Сорокін, Анатолій Іванович (My University, 2017)
Проаналізована робота оборотних систем водопостачання вітчизнаних бурякоцукрових заводів. Встановлено, що їх робота не завжди відповідає умовам зниження витрат свіжої води і скидання кількості стічних вод цукрового заводу. Показана можливість удосконалення оборотних систем водопостачання цукрових заводів. The work of reverse water supply systems of domestic sugar beet factories is analyzed. It was found that their work does not always meet the conditions for reducing fresh water consumption and the discharge of wastewater from a sugar factory. The possibility of improving the circulating water systems of sugar factories is shown.
Keywords: цукровий завод; система водопостачання; замкнута оборотна система водопостачання; sugar factory; water supply system; closed water circulation system